Effective approximation method for solving linear Fredholm-Volterra integral equations - Eshkuvatov Z.K.; Kammuji M.; Nik Long N.M.A.; Bachok M. Taib (American Institute of Mathematical Sciences, 2024)
Indexed by WOS/ Scopus